Commercialising eco-efficient nanotechnologies in the construction industry: The case of glass-processing in Finland - Christopher Palmberg (The Research Institute of the Finnish Economy (ETLA), 2009)
New and advanced process technologies are growing in importance for highly industrialized countries which increasingly have to compete with rapidly-developing, low-cost, countries. Nanotechnology is an interesting example in this context. It may evolve into a platform for industrial renewal in a broad range of sectors, and can also offer eco-efficient applications to address environmental concerns related to climate change. This paper assesses facilitating and inhibiting factors in the commercialisation and use of eco-efficient nanotechnology in the Finnish glass-processing and construction industry based on company case studies. The focus on the construction industry is motivated by its large contribution to economies while it also stands to gain significantly from new eco-efficient applications such as those enabled by nanotechnology. While there is an active community of nanotechnology-dedicated companies and research groups in this field, commercialization is inhibited by the absence of large and technologically progressive companies which could act as lead users, provide test markets, critical longer-term funding, and aid in the transition from R&D and piloting phases to industrial production. Public technology programs have provided a good basis for further developments and the construction industry could gain from nanotechnology once its benefits and value proposition to consumers and the general public become clearer.
Keywords: 330; nanotechnology; eco-efficiency; commercialisation; technological systems; glassprocessing; construction; Nanotechnologie; Öko-Effizienz; Kommerzialisierung; Forschungs- und Technologiepolitik; Glasindustrie; Bauwirtschaft; Finnland